The SPIRIT AND LAMENT - Minggus Minarto Pranoto (STT Amanat Agung, 2021)
Abstract: This article aims to explain about lament from the perspective of psychology and pneumatology. Psychology helps to explain psychic state of one who laments because of experiencing grief and bereavement; and pneumatology understands lament theologically by seeing and knowing God, self, and the world through the experience with the Holy Spirit in the believers. The two perspectives above are synthesized to understand the lament in the context of the life of believer. The method used is an interdisciplinary study between psychology and pneumatology by looking for connecting points that might fill and complement each other, especially in explaining the lament of believer. The thesis of this article is that the act of lament is a self-actualization of believer which can be explained from a psychology-pneumatology perspective and in lament the Holy Spirit transforms the life of believer. Lamentation can lead to an attitude of trust in God and the courage to continue with life again or, in psychologically term, a